The effect of Chinese martial arts Tai Chi Chuan on prevention of osteoporosis: A systematic review - Chow, Tsz Ho; Lee, Bo Yee; Ang, Adrian Bing Fung; Cheung, Veronica Yi Ki; Ho, Michelle Man Ching; Takemura, Saori (Journal of orthopaedic translation, 2018)
Tai Chi Chuan (TCC) is suggested to have beneficial effects on the musculoskeletal system. The aim of this systematic review is to evaluate the evidence of the effect of TCC on bone mineral density (BMD) and its potential for prevention of osteoporosis. A literature search was conducted using PubMed, Embase, and Cochrane databases from inception to January 2017. Randomized controlled studies, case–control trials, prospective cohort studies, and cross-sectional studies which evaluated the effect of TCC on BMD were selected without any subject or language restriction. Nine articles met the inclusion criteria, including seven randomized controlled trials (RCTs), one case–control trial (CCT), and one cross-sectional study, encompassing a total of 1222 participants. Five studies showed statistically significant improvements in BMD after TCC, three studies showed nonsignificant intergroup differences, and one study provided no statistical evaluation of results. The studies with nonsignificant results tended to have a shorter total duration of TCC practice. Apart from dual-energy X-ray absorptiometry (DXA), two studies additionally used peripheral quantitative computed tomography (pQCT) which showed statistically significant positive effects of TCC on preventing osteoporosis. TCC is beneficial to BMD and may be a cost-effective and preventive measure of osteoporosis. This beneficial effect is better observed in long-term TCC practice. The beneficial effect of TCC on BMD is suggested to be clinically translated to its potential for early rehabilitation and prevention of secondary osteoporosis in patients after surgical treatment of common osteoporotic fractures. The length of practicing TCC, the form and style of TCC, and the types of patient suitable for TCC are to be investigated in future studies.